Republic of Yemen : Poverty Update, Volume 1. Main Report - World Bank (Washington, DC, 2013)
Based on the analysis of the household budget survey, the report identifies a nationally widespread poverty, pervasive in rural areas, concentrated in four governorates. The factors that affect the risk of being poor in Yemen are lack of education, large households that include several children, geographical location that prevents access to income generation, and, lack of worker remittances from abroad. In addition, while public expenditures in social sectors (education and health), are mildly pro-poor, they do not address the magnitude of rural-urban, and gender gaps, and, by and large, social programs are urban biased, mostly benefiting the better-off. Incidentally, the benefit-incidence analysis of the safety nets, show that coverage is extremely limited, and that short-term downturns, and poverty vulnerabilities fail to be addressed. Most importantly, the report outlines that although programs under the second phase of the Social Development Fund are pro-poor, the inter-governorate distribution of both the Public Work Programs, and the Social Welfare Fund allocations, show no signs of pro-poor targeting. It is suggested to pursue structural, and institutional reforms, so as to introduce changes in the governance structure, that would ensure a pro-poor pattern of growth, one that would not widen the gap between the poor in urban vs. rural areas. Moreover, public investments in the social sectors should be improved, and public expenditures for those sectors increased.